Pengaruh Fasilitas Perpustakaan terhadap Minat Baca Siswa Tingkat Sekolah Dasar - Didit Darmawan; Abidha Khoiroh (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
Reading is one method for improving personal abilities through understanding knowledge and information obtained from written texts. This study was conducted to assess the impact of library facilities on students' reading interest at the elementary school level. This study employed a qualitative approach. Data were collected using a literature study method derived from relevant scientific literature using qualitative data analysis methods related to